2016
DOI: 10.1038/ncomms11805
|View full text |Cite
|
Sign up to set email alerts
|

In vivo modulation of endothelial polarization by Apelin receptor signalling

Abstract: Endothelial cells (ECs) respond to shear stress by aligning in the direction of flow. However, how ECs respond to flow in complex in vivo environments is less clear. Here we describe an endothelial-specific transgenic zebrafish line, whereby the Golgi apparatus is labelled to allow for in vivo analysis of endothelial polarization. We find that most ECs polarize within 4.5 h after the onset of vigorous blood flow and, by manipulating cardiac function, observe that flow-induced EC polarization is a dynamic and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
120
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 57 publications
10
120
0
Order By: Relevance
“…As a matter of absence of thick actin‐bundles in the central compartment, we show that sheared APJ‐KD HUVEC exhibit reduced elasticity‐values and a reduced ability to stabilize the nucleus leading to cellular detachment. These results are in accordance with the recent findings of Kwon et al (), who only recently showed, that signaling through APJ is required for endothelial cell polarization and therefore for cytoskeletal adaption to fluid flow.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…As a matter of absence of thick actin‐bundles in the central compartment, we show that sheared APJ‐KD HUVEC exhibit reduced elasticity‐values and a reduced ability to stabilize the nucleus leading to cellular detachment. These results are in accordance with the recent findings of Kwon et al (), who only recently showed, that signaling through APJ is required for endothelial cell polarization and therefore for cytoskeletal adaption to fluid flow.…”
Section: Discussionsupporting
confidence: 94%
“…Increasing evidence suggests that some GPCRs can be activated by mechanical stress independently of their actual ligand (Chachisvilis et al, ; Zou et al, ). In this context, the apelin receptor (APJ), has been described to act independently of its ligand apelin (Kwon et al, ; Scimia et al, ) and is implicated in the migration of human ECs (Kidoya et al, ; Zeng, Wilm, Sepich, & Solnica‐Krezel, ). Kwon et al () only recently showed an apelin‐independent function of APJ in flow‐induced EC polarization in an in vivo zebrafish‐model and in human primary ECs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heart, which composed of vessels, valves, and chambers, pumps adequate blood to organs and tissues, then provides oxygen and nutrients to the whole body, as well as assists in the removal of metabolic wastes. Periodic dilatation and contraction of the heart is caused by a complicated interaction between biological electrocardiac signals and mechanical forces (Kwon et al, ). The heart vessels consist largely of endothelium, vascular smooth muscle and adventitia.…”
Section: Introductionmentioning
confidence: 99%
“…How and why blood flow and ALK1 signaling direct EC migration against the direction of flow is an area of active investigation. In vivo, arterial ECs in non-regressing vessels generally polarize against blood flow, with the golgi and microtubule organizing center positioned upstream (with respect to the direction of blood flow) of the nucleus, and migration against flow has been reported in the adult rat aorta and mouse yolk sac arteries [52, 194–198]. In the mouse retina, wall shear stress magnitude positively correlates with the degree of EC polarization against flow and EC density [199].…”
Section: Cellular Mechanisms Of Avm Developmentmentioning
confidence: 99%